Perancangan Gedung Baru Kampus Pelita Bangsa Dengan Konsep Green Arsitektur Modern - Soeroso, Yusdianto Haryo (Universitas Pelita Bangsa, 2021)
Pelita Bangsa University is one of the higher education institutions that has great potential to be developed, but according to the writer's experience as a student at Pelita Bangsa, the existing building design is very inadequate to create comfort for its users, which is the arrangement of space and aesthetics. The building design lacks architectural and environmental aspects. The new design is a solution to help Kampus Pelita Bangsa become a university worthy of being a forum for users of its buildings and facilities. The design of this building applies the green concept of Modern Architecture